2016
DOI: 10.4102/sajcd.v63i1.105
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hearing impairment within the Cape Town Metropolitan area

Abstract: BackgroundThere is a lack of data on the prevalence of hearing impairment in South Africa. Current data is unreliable as it is based on national census information which tends to underestimate the prevalence of hearing impairment.AimThe aim of this study was to estimate the prevalence of hearing impairment in the Cape Town Metropolitan area and to determine factors associated with hearing impairment.MethodA cross-sectional household survey involving 2494 partcipants from 718 households was conducted between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 31 publications
2
27
1
Order By: Relevance
“…Male gender and increasing age have been identified as risk factors for hearing impairment [29]. In our study we have found that number of male subjects with hearing loss was more as compared to females.…”
Section: Original Research Articlesupporting
confidence: 51%
“…Male gender and increasing age have been identified as risk factors for hearing impairment [29]. In our study we have found that number of male subjects with hearing loss was more as compared to females.…”
Section: Original Research Articlesupporting
confidence: 51%
“…Using a low cut-off such as 25 dB would identify milder HI and would produce a higher prevalence, whilst a pure tone cut-off at 40 dB would result in a lower prevalence as only moderate and severe HI would be identified [48]. The prevalence of HI in a population-based study from South Africa was estimated at 12.3% when using a cut off of 25 dB, while it was low at 4.6% when the cut off was 30 dB in children and 40 dB in adults [49]. Additionally, different mean ages of the study populations across studies will also lead to different prevalence across these studies, since HI prevalence was shown to increase with age [1]; therefore, the older the population, the higher the prevalence.…”
Section: Discussionmentioning
confidence: 98%
“…The protocol “Ear and hearing disorders survey” proposed by the World Health Organization (WHO) performed an investigation on “ear pain” 34 but it is worth mentioning that the objective of the protocol was wider than only determining the prevalence of hearing loss. Besides, studies of this nature that have followed this protocol 13 33 35 36 did not present “ear pain/ache” in their results. Among school-age individuals, between the ages of 5 and 14 years old in India, one of the most common ear, nose and throat problem reported was earache, in 8.67% of the sample, 37 which was lower than what was presented herein.…”
Section: Discussionmentioning
confidence: 98%